PENGARUH TEKNIK REFRAMING UNTUK MERUBAH PERSEPSI SISWA TERHADAP GURU BK MELALUI BIMBINGAN KELOMPOK DI SMK HASANAH PEKANBARU - Sally Melia Murfi; Rosmawati Rosmawati; Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to examine the effect of reframing techniques to improve students' perceptions of BK teachers at Pekanbaru Vocational High School. This type of research is quantitative research with the experimental method using the One-Group Pretest-Posttest Design research design. The measuring instrument used in this study is the scale of measuring student perceptions of BK teachers which consists of 45 items before validation, and after validation obtained 26 valid items with a validity of 0.460 and reliability of 0.885. The subjects of this study were 7 students who were identified as having a poor level of BK teacher perception. The data analysis technique used is non parametric statistical techniques using the Rank Spearman test. The results of the study prove that the research hypothesis is accepted. Therefore, the results of the Rank Spearman test obtained r = 0.807 while the correlation coefficient r2 was 0.651. Thus there is the effect of reframing technique on students' perceptions of BK teachers by 65.1% in Pekanbaru Vocational High School. From the results of the Wilcoxon test obtained (Asymp. Sig) 0.018 <0.05, it can be concluded that there are differences in student perceptions scores about counseling teachers before and after being given treatment in the form of reframing techniques.Key Words: Reframing, Student Perceptions, BK Teacher